Na+/Ca2 + Exchange and Pacemaker Activity of Interstitial Cells of Cajal - Zheng, Haifeng; Drumm, Bernard T.; Zhu, Mei Hong; Xie, Yeming; O’Driscoll, Kate E.; Baker, Salah A.; Perrino, Brian A.; Koh, Sang Don; Sanders, Kenton M. (Frontiers in Physiology, 2020)
Interstitial cells of Cajal (ICC) are pacemaker cells that generate electrical slow waves in gastrointestinal (GI) smooth muscles. Slow waves organize basic motor patterns, such as peristalsis and segmentation in the GI tract. Slow waves depend upon activation of Ca2+-activated Cl- channels (CaCC) encoded by Ano1. Slow waves consist of an upstroke depolarization and a sustained plateau potential that is the main factor leading to excitation-contraction coupling. The plateau phase can last for seconds in some regions of the GI tract. How elevated Ca2+ is maintained throughout the duration of slow waves, which is necessary for sustained activation of CaCC, is unknown. Modeling has suggested a role for Na+/Ca2+ exchanger (NCX) in regulating CaCC currents in ICC, so we tested this idea on murine intestinal ICC. ICC of small intestine and colon express NCX isoforms. NCX3 is closely associated with ANO1 in ICC, as shown by immunoprecipitation and proximity ligation assays. KB-R7943, an inhibitor of NCX, increased CaCC current in ICC, suggesting that NCX, acting in Ca2+ exit mode, helps to regulate basal [Ca2+ ]i in these cells. Shifting NCX into Ca2+ entry mode by replacing extracellular Na+ with Li+ increased spontaneous transient inward currents (STICs), due to activation of CaCC. Stepping ICC from -80 to -40 mV activated slow wave currents that were reduced in amplitude and duration by NCX inhibitors, KB-R7943 and SN-6, and enhanced by increasing the NCX driving force. SN-6 reduced the duration of clustered Ca2+ transients that underlie the activation of CaCC and the plateau phase of slow waves. Our results suggest that NCX participates in slow waves as modeling has predicted. Dynamic changes in membrane potential and ionic gradients during slow waves appear to flip the directionality of NCX, facilitating removal of Ca2+ during the inter-slow wave interval and providing Ca2+ for sustained activation of ANO1 during the slow wave plateau phase.